2018
DOI: 10.1016/j.pmedr.2018.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Daily Minutes of Unprotected Sun Exposure (MUSE) Inventory: Measure description and comparisons to UVR sensor and sun protection survey data

Abstract: One in five US adults will be diagnosed with skin cancer. As most skin cancers are attributable to sun exposure, this risk factor is an important target for research and intervention. Most sun exposure measures assess frequency of specific sun-protection behaviors, which does not account for the use of multiple, potentially overlapping sun-protection methods. In contrast, the Daily Minutes of Unprotected Sun Exposure (MUSE) Inventory assesses sun-protection behavior during self-reported activities, providing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…At the end of each day, an email provided a link to the survey administered via REDCap 17 . The daily Minutes of Unprotected Sun Exposure (MUSE) 18 survey was adapted with self‐report of sunburn of body areas and intensity and types of outdoor physical activities. Each day, participants were asked to report details of all outdoor activities performed between 6 am and 6 pm for more than 15 minutes, which is typical in most studies, since it is difficult to report every time an individual goes outdoors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of each day, an email provided a link to the survey administered via REDCap 17 . The daily Minutes of Unprotected Sun Exposure (MUSE) 18 survey was adapted with self‐report of sunburn of body areas and intensity and types of outdoor physical activities. Each day, participants were asked to report details of all outdoor activities performed between 6 am and 6 pm for more than 15 minutes, which is typical in most studies, since it is difficult to report every time an individual goes outdoors.…”
Section: Methodsmentioning
confidence: 99%
“…The protection‐adjusted UV dose is a measure of personal sun exposure computed by integrating sun protection self‐reports 18 with UV sensor data for a specific outdoor activity. The UV exposure recorded by the sensor was adjusted for sun protection use for face, forearms, lower legs, and body (J/m 2 ) and for each unique activity using the following methodology: For each unique (non‐overlapping) activity k , let τ k = “time spent in hours in activity”.…”
Section: Methodsmentioning
confidence: 99%
“…The study smartphone was only used to upload the data, and participants did not need to carry the device with them all day. They were emailed a link containing the Daily Minutes of Unprotected Sun Exposure (MUSE) Inventory self-report questionnaire to report their outdoor activities and sun protection habits at the end of each day [16]. Participants were sent daily reminders and instructions for performing the data upload and completing the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…We will provide a commercially available UVR-sensor-enabled wrist wearable device to all participants, Shade, 2nd generation, which was developed in collaboration with the National Health Institutes (National Cancer Institute). Shade reported significantly more accurate UVR measurements than similar devices [ 18 ], and melanoma survivors have previously reported that the first version of the device was easy to use [ 19 ]. In addition to accurately measuring UVR exposure in a manner that does not rely on self-report and memory, Shade includes a mobile app that helps users set daily limits that take into account UVR intensity, time of exposure, and sunscreen application.…”
Section: Interventionsmentioning
confidence: 99%